Relationship Between Foreign Direct Investments and Capital Flight in Kenya: 1998-2018 - Mercy Wairimu Mwangi; Amos Njuguna; George Achoki (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
The study established the relationship between Foreign Direct investments and Capital Flight in Kenya over the period 1998 to 2018. Quarterly time series data for calculation of capital flight and Gross Domestic Product growth rate, inflation and Foreign Direct investments were collected from the Central Bank of Kenya and Kenya National Bureau of Statistics. Two Autoregressive Distributed-lagged model models were fitted. Regression coefficients for FDI were 0.44 and -0.040 in the short run and -0.501 in the long run. The p values were 0.008 and 0.015 and 0.654 respectively. The results indicated that a 1 % increase in current quarters FDI would lead to a 0.44% increase in capital flight and a 1% increase in previous quarters FDI would lead to a decrease of 0.040% in capital flight. Regression results showed a coefficient of 0.006 and - 0.004 for Gross Domestic Product growth rate in the short run, and 0.038 in the long run. The p values were 0.422, and 0.638 and 0.749 respectively meaning that Gross Domestic Product growth rate and the capital flight had no significant relationship. Regression results showed a coefficient of -0.001 and -0.005 for inflation in the short run and -0.088 for inflation for the long run. The p values were 0.844 and 0.363 and 0.253 respectively. This indicated that inflation and the capital flight had an insignificant relationship. The study recommends that government adopts strategic management on FDI inflow transactions to avoid possible leakages of the same money going out as capital flight.